Epilepsy surgery for children and adolescents: evidence-based but underused. (July 2022) - Cross, J Helen; Reilly, Colin; Gutierrez Delicado, Eva; Smith, Mary Lou; Malmgren, Kristina
Summary: Paediatric epilepsy surgery is an increasingly used evidence-based management option with low risks for complications. Developments in neuroimaging techniques and other advanced diagnostics have widened the spectrum of children who could benefit from the procedure, and surgery is now considered a standard management approach for epilepsy. Available data indicate that early surgery improves outcomes. Despite these considerable advances, epilepsy surgery in children is still underused. In this Review, we summarise the indications, patient selection, principles of presurgical investigations, optimal timing, and types of epilepsy surgery. We also examine comprehensive outcomes after surgery, including seizure outcomes, complications, cognition, neurodevelopment, vocational outcome, and health-related quality of life of children and their parents. Successful epilepsy surgery could lead to improvement in all these areas. Children should, therefore, be referred early for evaluation in an appropriately competent centre.